Pengaruh Profitabilitas, Leverage, dan Ukuran Perusahaan terhadap Manajemen Laba pada Industri Manufaktur Rokok Terdaftar di Bursa Efek Indonesia - Apriliani, Rahmania; Rakhmanita, Ani (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
Earnings Management is an intentional intervention by management in the profit determination process. The purpose of this study is to determine the effect of profitability, leverage and Firm size on earnings management. The population of this study consists of five manufacturing companies listed on the Indonesia Stock Exchange (IDX) between 2017-2021. Using sampel jenuh technique. The analysis tool is multiple linear regression, where previously the classical assumption test was carried out. Based on the test, it shows that Profitability has a positive and significant effect on Earnings Management, meaning that the higher the profits obtained by the company, the higher the Profit Management practices carried out by the managers. Leverage has no significant effect on Earnings Management, meaning that the greater the leverage a company has, the less likely the company is to practice earnings management, this is because a higher leverage ratio indicates an unfavorable financial situation for the company, making creditor supervision more stringent and financial risk higher. firm size has no significant effect on Earnings Management, meaning that the company is under strict supervision from the government, analysts and investors who run the company, causing managers to not dare to practice Earnings Management. Keywords: Profitability, Leverage and Company Size